Evidence of differences in trypanosusceptibility in East African Zebu cattle - Rowlands, G.J.; Mulatu, W.; D'Ieteren, G.D.M.; Nagda, S.M. (OAU/STRC, 1995)
An average of 840 East African Zebu cattle have been monitored in the Ghibe valley, south west Ethiopia since 1986. Despite a high prevalence of drug resistance, regular Berenil treatment appears to have maintained these cattle at reasonable levels of productivity. However, when corrected for frequencies of parasitaemia and treatment, there was significant associations between the PCV maintained by an individual and its productivity in terms of growth rate, calving interval or risk of abortion. For example, there was an average reduction in calving interval of 8.4 + 2.6 (se) days for each percent unit increase in PCV maintained during the first 5 months post partum. Similarly, there was a decrease in abortion rate of 0.8 + 0.3 percent unit for each percent unit increase in PCV maintained during the last 3 months of pregnancy. Despite deficiencies in these data brought about by the high levels of drug resistance, dam-offspring regression analysis indicated genetic associations between dam and offspring PCV when corrected for parasitaemia and treatment frequency. In other words, cows with abilities to maintain PCVs at higher levels than others appeared to pass on this same characteristic to their calves, particularly once calves approached two years of age. The co-heritability between the PCV of a dam and the PCV of her two year old offspring measured simultaneously over a 6-month period was 0.43 + 0.16 when corrected for frequencies of parasitaemia and treatment. These results demonstrate individual differences in the susceptibility of cattle to the effects of trypanosomiasis in this environment.